Low Prevalence of Anti-DFS70 Antibodies in Children With ANA-Associated Autoimmune Disease - Freudenhammer, Mirjam; Salzer, Ulrich; Heselich, Aileen; Hufnagel, Markus; Janda, Ales (Frontiers in Pediatrics, 2022)
Introduction: Anti-DFS70 antibodies occur in healthy individuals with various medical conditions. Unlike other anti-nuclear autoantibodies (ANA), they are not associated with systemic autoimmune disease in adult patients. To date, only a few studies have addressed the prevalence and/or clinical relevance of anti-DFS70 autoantibodies in children with and without autoimmune disease. Methods: Included in this retrospective cross-sectional mono-centric study were 308 pediatric patients with suspected or known autoimmune conditions who had a positive ANA in indirect immune fluorescence (IIF) screening and who were screened for anti-DFS70 antibodies by extractable nuclear antigen antibodies (ENA) immunoblot. Patients were assigned to four different diagnostic categories according to their diagnosis in the corresponding medical record: a) absence of autoimmune or rheumatic disease (noARD, n=116); b) suspected autoimmunity without definitive diagnosis (sAI, n=48); c) other rheumatic disease (ORD, n=115); and d) ANA-associated autoimmune disease (AARD, n=29). Results: The prevalence of anti-DFS70 antibodies in the overall cohort was 33.8%. Among children without ARD (46.6%, 54/116), prevalence was significantly higher than among children with ORD (23.7%, 27/115, p=0.0003) or AARD (17.2%, 5/29, p=0.0054). Among all of the anti-DFS70 positive patients with AARD, other autoantibodies were found in the ENA immunoblot. In contrast, among anti-DFS70 positive patients with ORD (11.5%, 4/27), sAI (33,3%, 6/18) and noARD (16.7%, 9/54), other autoantibodies infrequently were detected (p=0.0005). Patients with uveitis rarely were positive for anti-DFS70 antibodies (7.7%; 1/13). No association was found between anti-DFS70 antibodies and a history of allergic conditions (p=0.51). The concordance between a typical DFS pattern in IIF and the detection of anti-DFS70 antibodies by immunoblot was 59.3%. Conclusion: As with adults, the higher prevalence of anti-DFS70 among children without autoimmune disease confirms the mutual exclusion for this autoantibody in the pathogenesis of ARD. Among ANA-positive children, monospecific anti-DFS70 antibodies may help to discriminate between AARD and not-AARD-related conditions.